THE EFFECT OF RTV SILICON RUBBER COATING ON LEAKAGE CURRENT CHARACTERISTICS OF 150KV LONGROD INSULATORS - Nugroho, Alfiansyah
This study examines the impact of RTV (Room Temperature Vulcanizing) silicone rubber coating on leakage current characteristics of 150 kV long-rod insulators, with an emphasis on improving insulation performance under challenging environmental conditions, such as pollution and high humidity. Insulators are important components in electric power transmission systems, especially in outdoor environments that are vulnerable to various external factors. In polluted or wet environments, insulators often experience decreased performance due to the emergence of leakage currents that can disrupt the stability of the electrical system and increase the risk of equipment damage. Coating insulators with coating materials such as RTV silicone rubber aims to minimize these negative effects, by increasing the surface hydrophobicity and reducing the distortion of electrical signals generated by leakage currents. Experimental evaluations were carried out on two different groups of insulators, namely insulators coated with RTV silicone rubber and uncoated insulators, with each group tested under polluted and clean conditions. The uncoated insulator group served as a control to compare the effectiveness of RTV silicone rubber coating. Some of the characteristics analyzed in this study include insulation resistance, hydrophobicity, surface temperature, leakage current, total harmonic distortion (THD), and the cross product of the effective value (RMS) of the leakage current. These characteristics were chosen because they are very relevant in determining the performance of the insulator in a difficult environment. The results showed that the RTV silicone rubber coating significantly improved the insulating performance of the insulator. In the coated insulator, the measured insulation resistance was much higher compared to the uncoated insulator, even under polluted conditions. This indicates that the RTV coating provides an iv additional layer of effective protection against contaminants and moisture, thereby reducing the risk of the formation of conductive paths on the insulator surface. With higher insulation resistance, the potential for damaging leakage currents is also reduced. In addition, the RTV coating also proved to be very effective in maintaining the hydrophobicity of the insulator surface. Hydrophobicity refers to the ability of a material to repel water, which in the context of insulators is very important to prevent the formation of a water film on the surface that can cause leakage currents. In uncoated insulators, especially in contaminated conditions, the surface hydrophobicity tends to decrease drastically, making it easier for water and pollutants to adhere to the insulator surface and increasing the risk of leakage current. In contrast, in RTV-coated insulators, the hydrophobicity level remains high even in polluted environmental conditions, effectively preventing the formation of leakage current. This study also found that the THD associated with leakage current was significantly reduced in RTV-coated insulators. Harmonic distortion is a common problem in power systems and can cause equipment interference, reduce system efficiency, and increase the risk of damage. With the reduction in THD in coated insulators, the quality of the electrical signal produced is improved, making the system more reliable. This reduction in harmonic distortion is very important in maintaining the quality of distributed electricity, especially in high-voltage transmission systems. The cross-product of the RMS value of leakage current and THD shows that RTV-coated insulators have an optimal combination of low leakage current and minimal harmonic distortion, both in clean and polluted conditions. This shows that RTV coating not only helps to reduce the leakage current level, but also reduces signal distortion, which ultimately improves the overall performance of the insulator. Overall, this study confirms that RTV silicone rubber coating provides significant benefits in improving the performance of long-bar insulators at high voltages, especially under challenging environmental conditions such as pollution and high humidity. This coating not only increases the insulation resistance and maintains the surface hydrophobicity, but also reduces the harmonic distortion of the leakage current, thereby improving the overall reliability of the power system.